Globalization, universities and issues of sustainable human development - Pyle, Jean Larson, 1944-; Forrant, Robert, 1947-; Edward Elgar Publishing (Cheltenham, U.K. ; Northampton, Mass. : Edward Elgar, 2002)
This volume raises an important question: Given the fast-changing global economy and the challenges it presents, what is the role for the university as an institution promoting sustainable human development? The editors begin by outlining the changes associated with the recent wave of globalization, particularly transformations in the relative power of institutions internationally. They analyze the constraints universities face in industrialized and developing countries in promoting sustainable human development.
pt. 1. Globalization and the challenges confronting the university -- pt. 2. Answering the challenge : the university, knowledge creation and the sustainable human development process.
Includes bibliographical references and index.
Keywords: Universities and colleges -- Economic aspects -- Cross-cultural studies; Economic development -- Effect of education on -- Cross-cultural studies; Education and globalization -- Cross-cultural studies; Electronic books